2014
DOI: 10.1051/0004-6361/201322356
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the dynamical structure of pulsating stars

Abstract: Context. High-resolution spectroscopy is a powerful tool to study the dynamical structure of a pulsating star's atmosphere. Aims. We aim at comparing the line asymmetry and velocity of the two δ Sct stars ρ Pup and DX Cet with previous spectroscopic data obtained on classical Cepheids and β Cep stars. Methods. We obtained, analysed and discuss HARPS high-resolution spectra of ρ Pup and DX Cet. We derived the same physical quantities as used in previous studies, which are the first-moment radial velocities and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Another explanation could be secular radius variations; however, V335 Pup exhibits a reversal of the modulation, which may point to a recurrent phenomenon. Another possibility are non-radial pulsations that may manifest themselves as cycle-to-cycle variations in RVs (Kovtyukh et al 2003;Nardetto et al 2014). Strange pulsation modes (Buchler et al 1997;Buchler & Kolláth 2001) could also provide an explanation, since the predicted amplitudes are similar to the observed modulations.…”
Section: Discussionmentioning
confidence: 87%
“…Another explanation could be secular radius variations; however, V335 Pup exhibits a reversal of the modulation, which may point to a recurrent phenomenon. Another possibility are non-radial pulsations that may manifest themselves as cycle-to-cycle variations in RVs (Kovtyukh et al 2003;Nardetto et al 2014). Strange pulsation modes (Buchler et al 1997;Buchler & Kolláth 2001) could also provide an explanation, since the predicted amplitudes are similar to the observed modulations.…”
Section: Discussionmentioning
confidence: 87%
“…A summary of the available predictions and measurements of the p-factors of RS Pup and of the similar long-period Cepheid P. Kervella et al: Projection factor of the long-period Cepheid RS Pup Burki et al (1982) 1.36 1.36 Hindsley & Bell (1986) 1.341 1.343 Gieren et al (2005) 1.337 ± 0.038 1.347 ± 0.037 Groenewegen (2007) a 1.270 ± 0.050 1.270 ± 0.050 Laney & Joner (2009) 1.196 ± 0.038 1.201 ± 0.036 Storm et al (2011) 1.249 ± 0.105 1.262 ± 0.101 Neilson et al (2012) 1.140 ± 0.003 1.146 ± 0.003 Groenewegen (2013) 1.112 ± 0.030 1.128 ± 0.030 Nardetto et al (2014a) 1.181 ± 0.019 1.186 ± 0.018…”
Section: Discussionmentioning
confidence: 99%
“…A calibration of the p-factor of the intrinsically brightest Cepheids is therefore highly desirable. Theoretical studies (e.g., Neilson et al 2012) indicate that the pfactor may vary with the period, but the dependence differs between authors (Nardetto et al 2014a;Storm et al 2011;Breitfelder et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…But Antoci et al (2013) accepted the surface gravity of g log = 3.8 ± 0.2 and were surprised by the absence of solar-like oscillations at a frequency near 43 cd −1 that are predicted using this high value of surface gravity. Nardetto et al (2014) found the surface gravity and the effective temperature of ρ Pup to be equal to g log = 3.42 ± 0.14 and T eff = 6650 ± 100 K, respectively.…”
Section: Chemical Composition Of R Pupmentioning
confidence: 95%
“…Recently, Nardetto et al (2014) analyzed 359 spectra of ρ Pup observed during 5 nights with a spectral resolving power R = 115,000 at the HARPS spectrograph installed at the 3.6 m ESO telescope in La Silla. The exposure times were set as 30 s. The dominant mode of pulsation with frequency 7.098 days −1 with a semiamplitude of the radial velocity curve slightly less than 10 km s −1 and an additional mode with frequency 7.900 days −1 and semiamplitude 0.281 km s −1 were found.…”
Section: Chemical Composition Of R Pupmentioning
confidence: 99%